A critical review on production of biopolymers from algae biomass and their applications. (June 2021) - Kartik, Ashokkumar; Akhil, Dilipkumar; Lakshmi, Divya; Panchamoorthy Gopinath, Kannappan; Arun, Jayaseelan; Sivaramakrishnan, Ramachandran; Pugazhendhi, Arivalagan
Graphical abstract: Highlights: Importance of algal biomass in development of biopolymers. Production routes and advancements in isolation techniques. Applications of unexplored microalgal biopolymers were discussed. Future research directions could be the new road map for the biopolymer research. Abstract: Algae is abundantly present in our ecosystems and can be easily extracted and used for production of biopolymers. Algae does not produce any anthropogenic, harmful effects, has a good growth rate, and cultivable in wastewater. This literature elucidates the potential of algae biomass by comparing various seaweed and microalgae strains. The routes for biopolymer production were portrayed and their novel methods of isolation such as microwave assisted, ultrasound assisted, and subcritical water assisted extraction are discussed in detail. These novel methods are observed to be highly efficient compared to conventional solvent extraction, with the microwave assisted and ultrasound assisted processes yielding 33% and 5% more biopolymer respectively than the conventional method. Biopolymers are used in variety of applications such as environmental remediation, adsorbent and antioxidant. Biopolymer is shown to be highly effective in the removal of potentially toxic elements and is seen to extract more than 40 mg PTE/g biopolymer.